Modelo teórico del proceso de desarrollo de ingeniería electrónica (2019)
A theory is a common conceptual framework for structuring and organizing phenomena and knowledge in a concise and precise way. Electronic engineering endeavor (EEE) is the phenomenon in which a team solves an electronic system according an opportunity. Practitioner support such phenomenon by interest theories of endeavor mainly describing it in textual form and with partial coverage. Such descriptions address EEE approach, general management approach, and EEE analogous field approach like software engineering. Despite the availability of such theories, people report problems related to the endeavors and EEE in the state of the art. In studies of this field, authors reveal that most of the projects evaluated are delayed or canceled. Such difficulties are related to changes or breaches in scope, cost overruns, delays and endeavor cancellation. Some authors analyze causes of challenges and they attribute them to an EEE immature understanding and a lack of a general knowledge representation mechanism of EEE. Such authors declare the need for improving the theory related to such phenomenon and having better tools to deal with it. In this PhD Thesis we propose an EEE Conceptualization, an Endeavor Theory, and its application to EEE to produce the theoretical model of electronic engineering development processes, identifying their premises, constructs, and propositions. We use a method consisting of a literature review, EEE conceptualization, conceptual verifications, expert judgment, and synthesis of theories. We validate this PhD Thesis with one case study carried out in research and development center. This PhD Thesis is a first common language approximation improving communication between professionals, covering the aforementioned approaches, including improvement and unification in a formal description with terminological coherence. Description has a quantitative intrinsic interpretation and a qualitative facilitating its adoption, compatible with the state of the art. This PhD Thesis is a thinking framework and a general knowledge representation mechanism of EEE, scalable to other domains particularly to software engineering and Essence standard, and a contribution to a better understanding and performance of endeavor and EEE.